Effect of cropping systems on heavy metal distribution and mercury fractionation in the Wanshan mining district, China: Implications for environmental management. (1st August 2014) - Wang, Jianxu; Feng, Xinbin; Anderson, Christopher W.N.; Qiu, Guangle; Bao, Zhengduo; Shang, Lihai
Abstract The authors studied the concentration of heavy metals and mercury fractionation in contaminated soil in 2 agricultural land use systems (paddy rice and dry land) at the Wanshan mercury mine in China. The average concentrations of chromium, lead, copper, nickel, and zinc were generally lower in paddy rice soil relative to corn field soil. Soil under corn field production was slightly contaminated with lead (22–100 mg/kg), copper (31–64 mg/kg), and nickel (22–76 mg/kg) and moderately contaminated with zinc (112–635 mg/kg). In both soils, correlation of these metals with the titanium concentration in the soil indicates a geogenic origin for each metal (lead, r = 0.48; copper, r = 0.63; nickel, r = 0.47; zinc, r = 0.48). The mercury and antimony concentration in soil was high under both cropping systems, and future remediation efforts should consider the potential environmental risk presented by these metals. The concentration of bioavailable mercury in soil ranged from 0.3 ng/g to 11 ng/g across the 2 cropping systems. The majority of mercury (>80%) was associated with organic matter and the residual fraction. However, soil under paddy rice production exhibited a significantly lower concentration of Fe/Mn oxide–bound mercury than that under corn field production. This may be a function of the reduction of Fe/Mn oxides in the paddy rice soil, with the subsequent release of adsorbed metals to the soil solution. Sequential change from corn field to paddy rice production, as practiced in Wanshan, should therefore be avoided. Mercury adsorbed to Fe/Mn oxides in corn field soil potentially could be released into the soil solution and be made available for biomethylation under the flooded water management conditions of a rice paddy. Environ Toxicol Chem 2014; 33:2147–2155. © 2014 SETAC